Word number, level, and frequency in current English course books: Corpus study - Ari Nurweni; Endang Komariah (UPT Bahasa Universitas Tanjungpura, 2023)
Introducing the right English words in an adequate number and levels to beginner EFL learners is of paramount importance to enable them to communicate and develop their English further. This corpus study is meant to investigate the number and levels of English words, and their frequency of occurrences in a set of three official English course books for Indonesian junior high school students of the seventh to ninth grades, published by The Indonesian Ministry of Culture and Education. The study was conducted by converting each of the three English books into MS Word documents, eliminating the non-English and very common loanwords, saving each course book in plain text, and processing the plain text using a word frequency analysis program. The results show the English course books contain (1) a sufficient number of English words for comprehension of simplified pictured texts but not for authentic texts, (2) the high-frequency words that belong to the first, second thousand, and academic words, each of which is in an inadequate number, and (3) the frequency of word occurrences in the three books that is unlikely to lead to incidental word learning if no further efforts are made by the students and teachers.